MODERN METHODS OF SELECTING MAINTENANCE SIGNIFICANT ITEMS OF AIRCRAFT AVIONICS EQUIPMENT - D. B. Rychenkov (Научный вестник МГТУ ГА, 2016)
The article discusses the selection of functionally important elements of aircraft avionics using the procedures of MRB and AVPO.